2015
DOI: 10.1590/0100-67622015000400006
|View full text |Cite
|
Sign up to set email alerts
|

Ajustamento Osmótico Em Mudas De Jatobá Submetidas À Salinidade Em Meio Hidropônico

Abstract: RESUMO -Em ambientes naturais, a salinidade representa grande empecilho ao desenvolvimento dos vegetais. Visando à melhor compreensão dos efeitos que ela provoca na fisiologia de espécies arbóreas nativas, este trabalho objetivou avaliar o comportamento fisiológico de mudas de jatobá (Hymenaea courbaril L.) submetidas à salinidade em meio hidropônico. Portanto, um experimento foi realizado em casa de vegetação do Laboratório de Fisiologia Vegetal da Universidade Federal Rural de Pernambuco, adotando-se um deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…Del Amor et al (2000) report that this nutrient can attenuate the effect of saline stress on cultures due to competition 152 Formation of soursop… VELOSO, L. L. S. A. et al in absorption between the nitrate and chloride ions, that an increase in nitrate concentration in the root zone may inhibit increased absorption of chloride by the plant. Additionally, the accumulation of these organic solutes inside the cell may increase the osmotic adjustment capacity of the plants, helping and favoring the increment of tolerance to certain levels of water and salt stress (NASCIMENTO et al, 2015) producing better-quality seedlings to plant the orchard, increasing the establishment rate at the field, which is of great importance, especially in the first months after planting, when they are subjected to more-adverse environmental conditions (OLIVEIRA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Del Amor et al (2000) report that this nutrient can attenuate the effect of saline stress on cultures due to competition 152 Formation of soursop… VELOSO, L. L. S. A. et al in absorption between the nitrate and chloride ions, that an increase in nitrate concentration in the root zone may inhibit increased absorption of chloride by the plant. Additionally, the accumulation of these organic solutes inside the cell may increase the osmotic adjustment capacity of the plants, helping and favoring the increment of tolerance to certain levels of water and salt stress (NASCIMENTO et al, 2015) producing better-quality seedlings to plant the orchard, increasing the establishment rate at the field, which is of great importance, especially in the first months after planting, when they are subjected to more-adverse environmental conditions (OLIVEIRA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nascimento (2009) reported that H. courbaril performs osmotic adjustment when exposed to water stress. Nascimento et al (2015) verified that jatobá plants in water deficit condition present a osmotic adjustment due to the increase of the turgor in the leaf. Stigonocarpa) due to the weather.…”
Section: Concentrations Of Proline and Glycine-betaine (Gb)mentioning
confidence: 72%
“…Em relação ao K + observou -se declínio significativo na acumulação desse ião (43,21% para CNPAPM -X; 64,82% para CNPAPM -III) em folhas do tratamento mais severo quando comparado com o controle. A redução na concentração de K + com o aumento das concentrações salinas também foi observada em J. curcas por Silva et al (2009) e Cunha et al (2013), em maracujazeiro amarelo (Cruz et al, 2006), em jatobá (Nascimento et al, 2015) e em faveleira (Oliveira et al, 2012).…”
Section: Resultsunclassified